Estimativa populacional e distribuição espacial de Callithrix aurita (É. Geoffroy, 1812) em uma área de proteção ambiental, Serra do Japi, Cabreúva-SP - Gonçalves Junior, João Mendes (Universidade Federal de São Carlos, 2020)
Despite the devastation to which it was subjected, Atlantic Forest is still home to very high levels of biological diversity and endemism. From Callitrichidae family, the endangered buffy-tufted-ear marmoset (Callithrix aurita É. Geoffroy, 1812) is endemic to the Atlantic Forest of southeastern Brazil and is the least known. Its restricted distribution, the destruction of its habitat and competition with invasive species, have corroborated the population decline, increasing the risk of extinction of the species. In view of this scenario, this work aimed to collect data in situ to analyze the current situation of the groups of buffy-tufted-ear marmoset, evaluating their distribution, estimating density and population abundance in a remnant of seasonal semideciduous forest in Serra do Japi, in the municipality of Cabreúva-SP. We sampled four transects that totaled 17,6 linear km. In each transect, a division of consecutive points was established every 200 m, totaling 81 sample points, where the species' vocalization was reproduced with the use of playback. Once the presence of animals was detected, the location (GPS), the estimated distance from the observation point and the number of individuals in the group were recorded. Data collection was carried out using the monitoring method throughout the year, from June 2018 to June 2019, and data were twice a month collected. During the 13 months of monitoring 415,4 km were covered and 15 groups of buffy-tufted-ear marmoset were identified, among them, two presented hybrid individuals. It was calculated a density of 1,06 groups/km² (7,6 ind./km²) and an abundance of 4.6 groups/10 km. The groups were sampled in almost the entire length of the transects and the average number of individuals sighted was 7,2 ± 1,8 individuals/group (± SD; N = 191). These values when compared to the literature are relatively high, indicating this protection area is an important region for the conservation of the species. This is a pioneering work to present data of population estimates of buffy-tufted-ear marmoset inhabiting Serra do Japi. Despite the presence of groups in the area, future studies monitoring these populations are essential, since they are subject to several threats (loss and fragmentation of habitat, invasive species, etc.).
Population estimate and spatial distribution of Callithrix aurita(É. Geoffroy, 1812) in a protected area, Serra do Japi, Cabreúva-SP
Keywords: Sagui-da-serra-escuro; Mata Atlântica; Densidade populacional; Conservação; Buffy-tufted-ear marmoset; Atlantic Forest; Population density; Conservation; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONSERVACAO DAS ESPECIES ANIMAIS